STUDENTS' MATHEMATICAL CREATIVE THINKING SKILLS IN SOLVING PISA PROBLEMS: A CASE IN INDONESIA - Putri, Riska Yolanda; Puspaningtyas, Nicky Dwi; Hadi, Windia (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This study analyzes students' creative thinking skills in solving PISA questions involving spatial and geometric content. A descriptive qualitative approach was used, selecting three groups of students based on mathematical ability: high, medium, and low. Data were collected through tests, interviews, and documentation. The test consisted of three PISA items designed to assess students' creative thinking indicators: fluency, flexibility, originality, and elaboration. The conclusions of this study show that students with high mathematical ability exhibit a high level of creative thinking, as evidenced by the fulfillment of all indicators: fluency, flexibility, elaboration, and originality. Students with moderate mathematical ability demonstrate limited or moderate creative thinking, fulfilling only the fluency and originality indicators, while elaboration and flexibility are not optimal. Students with low mathematical ability fulfill only the originality indicator, with low fluency and elaboration, and do not demonstrate flexibility.